Between Philosophy and Ideology Disputes on Philosophy in the Post-war Polish Science: Disputes on Philosophy in the Post-war Polish Science - Konstańczak, Stefan (Folia Philosophica, 2017)
The article presents the situation of Polish philosophy in the post-war period, when there was an attempt to dominate science by Marxists. The culmination of this process happened during the session of the First Congress of Polish Science (29.06—2.07.1951). The Congress had a symbolic meaning for the Polish philosophy because along with the Congress independent philosophical magazines were closed, pre-war professors were dismissed, and also a social scientific movement was liquidated. The state authorities considered philosophy, next to law and history, as disciplines which were essential for the promotion of Marxist ideology. As a result, the pre-war research and didactic professors at universities were replaced by “educated Marxists”, for whom philosophy was only a discipline which served for ideological tasks. For many years it changed the way of practicing philosophy in Poland, the consequences of which can be felt to this day.